The Psychometric Features of the Turkish Version of the Ageism Survey and the Frequency of Ageism - ERGÜN, AYŞE; ŞİŞMAN, FATMA NEVİN; KADIOĞLU, HASİBE; GÜR, KAMER; KOLAÇ, NURCAN; EROL, SAİME (ELSEVIER TAIWAN, 2016)
Background: This study was conducted to adapt the ageism survey to the Turkish language and culture and to determine the frequency of occurrence of ageism. Methods: The study population consisted of 236 individuals aged 50-95 years. The cultural adaptation of the ageism survey was carried out through the method of translation/back-translation and the validity of the instrument was tested for content and construct validity; its reliability was tested by internal consistency analysis. Results: The mean age of the respondents was 64.44 +/- 9.57. The content validity index for the ageism survey was found to be 0.89 and Cronbach a value was 0.86. Item-total correlation values for all of the items were over 0.31. Of the participants, 82.5% reported being confronted with some kind of discriminatory behavior at least once. Conclusion: It was established that the ageism survey is appropriate to the Turkish language and culture and that it is a valid and reliable instrument. Copyright (C) 2016, Taiwan Society of Geriatric Emergency & Critical Care Medicine. Published by Elsevier Taiwan LLC.
Keywords: ageism; instrument; prevalence; reliability; validity